6(9)-2(9-5)=46

Simple and best practice solution for 6(9)-2(9-5)=46 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(9)-2(9-5)=46 equation:


Simplifying
6(9) + -2(9 + -5) = 46

Multiply 6 * 9
54 + -2(9 + -5) = 46

Combine like terms: 9 + -5 = 4
54 + -2(4) = 46

Multiply -2 * 4
54 + -8 = 46

Combine like terms: 54 + -8 = 46
46 = 46

Add '-46' to each side of the equation.
46 + -46 = 46 + -46

Combine like terms: 46 + -46 = 0
0 = 46 + -46

Combine like terms: 46 + -46 = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| -2x+20=0 | | 83=q-17 | | 83=y-17 | | 2x+30=2x-35+x+15 | | y=5ln(x+3) | | -15=2t-21 | | 5X+4X+2+3X+10= | | 5(123.31)-20= | | 4y+9=13-2(y+3) | | 5(5)-4(5-3)=17 | | 2/3*n=24 | | n^(9/2)*n^(-5/2) | | 18+5w=8w | | 5(5)-4(-5-3)=17 | | 6x-18=7x+13 | | 15/2×1/3 | | 150x-3x^2=1000 | | x^2-21x+100=80 | | (4a^4)(b^4)(b^4)=(4ab)4 | | 24x+32x=32 | | 15/2×1/3×1/5 | | 11(11.21)-10= | | -9-b+b=-23 | | -8-12x=7-2x-6 | | 18a^3b^5+23b^2+5=0 | | 3(x-3/4)= | | .5x(5-7x)=8-(4x+6) | | 6p-5=7p+7-p | | h=-16t^2+100t+600 | | 15x^2-66x-45=0 | | 144+x^2=225 | | 84x^2-20xy+12x=0 |

Equations solver categories